Assesment of Organotin Contamination at the Gadani Shipbreaking Yard, Pakistan - Hassana, Safia; Siddiquia, Ghazala; Zhaob, Yanyan; Wangb, Xinhong (Asian Journal of Biological and Life Sciences, 2016)
Imposex is a well-documented sexual abnormality in female gastropods caused by tributyltins and triphenyltins leached into the marine environment from antifouling paints applied on submerged marine structures such as fishing nets and bouys. In the present study two bioindicator species of gastropods, Thais bufo and Thais rudolphi,were examined from the Gadani shipbreaking yard, Pakistan. The indices of imposex intensity, i.e., relative penis size index was higher in T. bufo (50.60%) as compared to T. rudolphi(17.01%). The vas deferens Sequence Index (VDSI) and incidence of imposex were 4.0%and 100% respectivly in both species. Chemical analysis revealed higher bioaccumulation of total butyltinsthan phenyltins. The body burden of diphenyltinwas greater than monophenyltins and triphenyltins. Similarly higher bioaccumulation of dibutyltinthan tributyltin and monobutyltinwas observed in both species with the exception of high content of tributyltin andmonophenyltin in T. bufo male and imposexrespectivly. This study therefore demonstrates that the potential influence of organotin contamination due shipbreaking activities can cause high bioaccumulation of TBT and 100% degree of imposexin both targeted species
Keywords: Bioaccumulation; Butyltins; Imposex; Phenyltins; Shipbreaking Yard; TBT; Tributyltin